Synergistic role of blood-labyrinth barrier permeability and endolymphatic hydrops: a comparative perspective in Ménière’s disease and vestibular migraine - Yin, Haozhe; Li, Hui; Zheng, Yifan; Jia, Yanlu; Shen, Bo; Sun, Yuanyuan; Sun, Shuning; Zhang, Yaoheng; Peng, Wenbo; Liu, Chunling (Frontiers in Neurology, 2025)
ObjectiveThis study compares the delayed gadolinium-enhanced MRI characteristics of Ménière’s disease (MD) and vestibular migraine (VM) to develop a multiparametric model that incorporates endolymphatic hydrops (EH), blood-labyrinth barrier permeability, and their asymmetry. Additionally, it investigates the correlations between these imaging features and hearing loss across various frequencies.MethodsA total of 79 patients—47 with MD and 32 with VM—were enrolled in the study between June 2023 and April 2025. All participants underwent a comprehensive medical history assessment, neurotologic evaluation, audiological testing, and a 3D SPACE FLAIR MRI conducted 4 h after the administration of intravenous gadolinium contrast agents. EH, the signal intensity ratio (SIR) of the cochlear basal turn, and the cochlear SIR asymmetry index (c-SIR AI) were assessed. Linear regression was employed to evaluate the contributions of EH and SIR to hearing loss. Additionally, a logistic regression model with ROC analysis was developed for diagnostic purposes.ResultsAll ipsilateral ears in the MD group exhibited EH, with median cochlear and vestibular EH grades of 2 (1, 2) and 1 (1, 2), respectively. These grades were significantly higher than those observed in the VM group, where the median grades were 0 (0, 1) for both cochlear and vestibular EH (both p < 0.001). MD demonstrated a unilateral predominance. The ipsilateral SIR and c-SIR AI were higher in MD compared to VM (1.39 ± 0.15 vs. 1.18 ± 0.18 and 17.24 ± 10.93 vs. 6.52 ± 3.74, both p < 0.001). In MD, both EH and SIR predicted low-frequency hearing loss; with SIR being the primary predictor (β = 68.717, p < 0.001). SIR also predicted high-frequency loss (β = 80.139, p < 0.001). In VM, SIR predicted thresholds across all frequencies, with the strongest correlation observed for high-frequency thresholds (β = 79.551, p < 0.001). A combined model (including cochlear EH, vestibular EH, SIR, and c-SIR AI) demonstrated high diagnostic performance, achieving a sensitivity of 76.6%, specificity of 100%, and an AUC of 0.954.ConclusionDelayed gadolinium-enhanced MRI of the inner ear facilitates the differentiation between MD and VM. The combination of EH, SIR, and c-SIR AI demonstrates excellent diagnostic performance. Notably, elevated SIR shows the strongest correlation with high-frequency hearing impairment, while cochlear EH primarily contributes to low- and mid-frequency hearing loss. By integrating imaging findings with audiological profiles, clinicians can accurately characterize cochlear pathology, enabling the development of tailored treatment strategies.